Southeast Asian images towards civil society? - Mulder, Niels (Silkworm Books, 2003)
This unusual study discloses the public discourse among educated, urban Southeast Asians in Thailand, Indonesia, and the Philippines, and considers how these people conceive of their society and its problems and process. It examines basic patterns of thought, the interpretation of observed behavior, the opinions of public intellectuals, and the diagnoses of novelists. Together these provide the basis for evaluating whether or not an activist civil society can develop. Because of the muddled situation prevailing in the countries under scrutiny, the emergence of a public committed to change seems to be a necessary condition for strengthening the society and civilizing the state. Will it happen?